Study of Gamma — irradiation effects on the Polymethylmethacrylate (PMMA) Using (PAL) Method - Abdullah, A. A. (Iraqi Journal of Physics, 2002)
Gamma - irradiation effect on polymethylmethacrylate (PMMA) samples has been studied using Positron Annihilation Lifetime (PAL) method. The orthopositronium (o-Ps) lifetime τ3, hence the o-ps parameters, the volume hole size (Vh) and the free volume fraction (Ꞙh) in the irradiated samples were measured as a function of gamma-irradiation dose up to 28.05 kGy. It has been shown that τ 3, Vh, and Ꞙh, are increasing in general with increasing gamma-dose, to reach a maximum percentage increment of 22.42% in τ3, 60% in Vh and 29.5% in Ꞙh, at. 2.55 kGy, whereas τ2 reaches maximum increment of 119. 7% at 7.65 kGy. The results suggest that gamma-irradiation induces structure changes in PMAM, causing degradation in the main chains, and the presence of oxygen Causes reduction in the amorphous regions ; oxygen and the peroxy radicals form cross-linking at reactive sites between neighboring chains, giving a net reduction of the degradation yield.